KEBIJAKAN PENDIDIKAN ISLAM ERA REFORMASI - Anas Tania Janari (STAI Ma'had Aly Al-Hikam Malang, 2021)
This article aims to find out about the policies implemented in the reform era. This can be seen in the application of Islamic education which can contribute to the progress of Muslims in all fields. It is said so because the curriculum applied includes the treatment applied in everyday life. In the reformation era, Islamic education got better after the end of the New Order era when Suharto stepped down from his presidency. With the improvement of the Islamic education system, new policies emerged with the times. The method used in this article uses a qualitative approach and this type of research is a literature review research. The results of the analysis show that the reform era was a major change made in the world of Islamic education. The education levels that have been raised are Madrasah Ibtidaiyah which is equivalent to elementary school, Madrasah Tsanawiyah which is equivalent to junior high school, and also Madrasah Aliyah which is equivalent to high school level. The largest Islamic educational institution is the Islamic boarding school, which is the biggest contributor to the development of Islamic education.